2011
DOI: 10.1074/jbc.m111.248203
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Bile Acid Pool Size with a Synthetic Farnesoid X Receptor (FXR) Agonist Induces Obesity and Diabetes through Reduced Energy Expenditure

Abstract: We evaluated the metabolic impact of farnesoid X receptor (FXR) activation by administering a synthetic FXR agonist (GW4064) to mice in which obesity was induced by a high fat diet. Administration of GW4064 accentuated body weight gain and glucose intolerance induced by the high fat diet and led to a pronounced worsening of the changes in liver and adipose tissue. Mechanistically, treatment with GW4064 decreased bile acid (BA) biosynthesis, BA pool size, and energy expenditure, whereas reconstitution of the BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
181
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(195 citation statements)
references
References 43 publications
9
181
2
3
Order By: Relevance
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 57%
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 57%
“…In line with our fi ndings, it has been reported that bile acids promote energy expenditure by TGR5 activation ( 12 ) and that a lowered bile acid pool size reduces energy expenditure ( 16 ). This led to the suggestion that BAS treatment would result in decreased energy expenditure ( 17 ).…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies suggested a role of bile acids in glucose and energy homeostasis. Mice fed a cholic acid (a bile acid)-supplemented diet had increased energy expenditure, preventing obesity and insulin resistance (21), although mice with reduced bile acids had decreased energy expenditure (20). Bhmt deletion resulted in increased cholate and taurocholate in adipose tissue and in increased taurocholate and glycocholate in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented as mean Ϯ S.E. VO 2 (20,21). Increasing bile acid pool size in mice increased energy expenditure (21), while decreasing bile acid pool size reduced energy expenditure, resulting in weight gain and insulin resistance (20).…”
Section: Table 1 Indirect Calorimetry Data Analysismentioning
confidence: 99%